HIJAB DAN GENDER: TELAAH KASUS LAKI-LAKI BERHIJAB MELALUI LENSA KONSELING ISLAM DI MASJID HUBBUL WATHON MATARAM - Hamzanwadi; St. Samsuduha; Hasriani, Andi (Universitas Islam Ahmad Dahlan, 2025)
The phenomenon of men wearing the hijab has become an issue that challenges the prevailing social, cultural, and religious norms in society. In the traditional Islamic perspective, the hijab is seen as an obligation for women as a form of obedience and self-protection. However, the emergence of men wearing the hijab raises critical questions about gender identity, self-expression, and understanding of religious teachings. This study aims to examine this phenomenon through an Islamic counseling approach with a focus on the psychological, spiritual, and social aspects of the client. This study uses a descriptive qualitative method with a case study approach to explore the motivations, backgrounds, and inner dynamics of individuals who choose to wear the hijab as men. The results of the study indicate that the use of the hijab by men is not always related to identity deviation, but can represent a spiritual search, a form of social criticism, or an existential expression that needs to be understood holistically. The Islamic counseling approach plays an important role in providing empathetic and non-judgmental assistance, while still being based on the values ​​of the Qur'an and As-Sunnah. This study encourages the development of new insights in Islamic counseling that are more inclusive of the diversity of individual expression in the modern era.